Skin healing in the terrestrial toad Melanophryniscus montevidensis (Philippi, 1902): an experimental approach - Victoria Machín Otheguy; José Manuel Verdes; Emilia Rossini; Mayra Severo; Francisco Kolenc; Claudio Borteiro (Revista de Biologia Neotropical, 2023)
We studied in this work the skin healing process in the terrestrial toad Melanophryniscus montevidensis. Wild specimens were acclimated in the laboratory, and an experimental skin wound of 1.5 mm diameter was made in the dorsum region under clove oil anesthesia, leaving the dermis exposed. Monitoring of the healing process by conventional histology was made up to 129 days. The epidermal protection of the wound was recovered after two days, and apparently, a complete recovery of dermal glandular structures was evident after 37 days. This feature includes the serous glands that play a relevant role in the defensive strategy of this species. No complications were recorded from the anesthetic procedure, not previously assessed in Melanophryniscus.